2021
DOI: 10.1155/2021/9360339
|View full text |Cite
|
Sign up to set email alerts
|

MKRN1 Ubiquitylates p21 to Protect against Intermittent Hypoxia‐Induced Myocardial Apoptosis

Abstract: Although chronic intermittent hypoxia- (IH-) induced myocardial apoptosis is an established pathophysiological process resulting in a poor prognosis for patients with obstructive sleep apnea syndrome, its underlying mechanism remains unclear. This study is aimed at exploring the role of makorin ring finger protein 1 (MKRN1) in IH-induced myocardial apoptosis and elucidating its molecular activity. First, the GSE2271 dataset was downloaded from the Gene Expression Omnibus database to identify the differentially… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 24 publications
0
7
0
Order By: Relevance
“…Lack of regenerative capacity, cardiomyocytes are replaced by collagen fibers after dying due to inflammation or injury, which eventually leads to myocardial remodeling. Therefore, apoptosis and ageing of the cardiomyocyte plays an essential role in the myocardial disease development, and the inhibition of apoptosis in myocardial ischemic disease shows to mitigate this process [ 21 , 22 ]. In the lncRNA Ftx dysfunction model, we identify multiple proteins involved in apoptosis, evidenced by the upregulation of ITGB1, HMGA2, KRAS and the downregulation of STAT3, RB1, LGALS3.…”
Section: Discussionmentioning
confidence: 99%
“…Lack of regenerative capacity, cardiomyocytes are replaced by collagen fibers after dying due to inflammation or injury, which eventually leads to myocardial remodeling. Therefore, apoptosis and ageing of the cardiomyocyte plays an essential role in the myocardial disease development, and the inhibition of apoptosis in myocardial ischemic disease shows to mitigate this process [ 21 , 22 ]. In the lncRNA Ftx dysfunction model, we identify multiple proteins involved in apoptosis, evidenced by the upregulation of ITGB1, HMGA2, KRAS and the downregulation of STAT3, RB1, LGALS3.…”
Section: Discussionmentioning
confidence: 99%
“…Makorin Ringinger Protein 1 (MKRN1) is an E3-type ubiquitin ligase. It has been shown that MKRN1 promotes p21 protein ubiquitination and proteasome pathway degradation, thereby preventing intermittent hypoxia (IH)-induced myocardial apoptosis ( 46 ). MKRN1 can disrupt p53 and thus apoptosis through ubiquitination ( 47 ).…”
Section: Discussionmentioning
confidence: 99%
“…MKRN1, an E3 ubiquitin ligase, plays a significant role in regulating disorders through the ubiquitination of substrate proteins. Bai et al found that MKRN1 could promote p21 protein ubiquitination and the proteasome pathway degradation to negatively regulate p21 expression, thereby preventing intermittent hypoxia-induced myocardial apoptosis [ 24 ]. Kotla et al found that MKRN1 expression was inhibited by TERF2IP S205 phosphorylation and it promoted endothelial cell activation and senescence, contributing to the development of atherogenesis [ 25 ].…”
Section: Discussionmentioning
confidence: 99%